MODERASI BERAGAMA MUHAMMADIYAH DI KABUPATEN YAPEN - Rakhmadi, Herlambang Dwi Prasetyo (Universitas Cokroaminoto Yogyakarta, 2024)
Yapen Regency is administratively included in the Province of Papua and has a diversity of ethnicities, races and religions. Facing the existing diversity, a wise and fair way is needed, namely religious moderation, religious moderation is the middle way in dealing with existing differences. Muhammadiyah as one of the religious community organizations based on Islam was present in Yapen in 2001 with the establishment of the Yapen Muhammadiyah Regional Leadership (PDM), religious moderation carried out by PDM Yapen through educational institutions and became the spearhead of Muhammadiyah propaganda. Muhammadiyah Serui Middle School was the beginning of PDM Yapen's struggle in implementing the values of religious moderation in Yapen and becoming a laboratory of religious moderation to spread diversity values, ideas of diversity, and messages of humanity.